Quatre mille marches - Chen, Ying (Collection Papiers collés, 2004)
« Romancière avant tout, Ying Chen a tout de même rédigé, au fil des ans, des textes dans lesquels elle tente de réfléchir simplement, modestement, en adoptant le mode de l’interrogation, du souvenir et de la lettre familière plutôt que celui de l’analyse ou de la théorie, à ce que sont pour elle - et peut-être pour ses lecteurs - la portée et la signification de son art, le sens de son itinéraire personnel de femme, d’exilée et d’écrivain, ou la place de la littérature dans le monde éclaté d’aujourd’hui. Il en résulte une série d’essais brefs, écrits dans une prose aussi sobre que directe, qui constituent d’une certaine manière l’accompagnement ou l’écho méditatif de cette parole qui se fait entendre dans ses romans et à travers la voix des personnages auxquels elle a donné vie. »
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; arts; asie; chine; cours; discipline; lit2815; lit3495; point de vue situé; premier cycle; périodes historiques; régions géographiques; thématiques; écriture des femmes*; études littéraires

Pour une théorie générale de l'exploitation. Deuxième partie: repartir du bon pied - Delphy, Christine (Mouvements, 2004)
Keywords: OFDIG; afrique; amériques; approches et analyses; asie; cours; cycles supérieurs; discipline; discours dominant; exploitation; fem9000; intersectionnalité; marxisme; ressource en ligne; régions géographiques; sciences de la gestion; systèmes d'oppressions; thématiques; travail; violences; économie; économie sociale

‘Who is the Developed Woman?’: Women as a Category of Development Discourse, Kumaon, India - Klenk, Rebecca M. (Development and Change, 2004)
This article analyses gendered discourses of development in rural North India, and addresses the usefulness of recent scholarship on development as ‘discourse’ for understanding connections between development and subjectivity. This scholarship is an excellent point of departure for exploring the contradictions inherent in the institutionalization of economic development and the global reach of its discourses, but it has focused primarily upon development as discourse at official sites of deployment, while paying less attention to how specific discourses and processes of development are appropriated by those constituted as beneficiaries of development. The under-theorization of this aspect has meant that the range of processes through which development projects may encourage new subject positions are poorly understood. By investigating what some women in rural Kumaon have made of their own development, this article contributes to emerging scholarship on development and subjectivity with an ethnographic analysis of the polysemic enthusiasm for development expressed by some of its ‘beneficiaries’.
Keywords: Kumaon; anthropologie; approches et analyses; asie; cours; discipline; développement; féminisme décolonial; histoire et politique; inde; pol4022; premier cycle; relations internationales; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; thématiques

Transnational migration theory in population geography: gendered practices in networks linking Canada and India - Walton-Roberts, Margaret (Population, Space and Place, 2004)
Geographers have recently suggested that transnational migration theory can contribute to the development of a critical population geography. What might such a critical population geography look like? In this paper I explore this in three ways. Firstly I offer some comments on why geographers have been slow to adopt a transnational focus on migration, and secondly I examine how gender has been underplayed in transnational literature. Thirdly I draw upon some examples from research on transnational immigrant networks between Canada and India. I focus on the specifics of Punjabi marriage migration networks to demonstrate how the practice of spousal selection has become globalised for certain diasporic communities. These examples offer a preliminary illustration of what a critical population geography, attuned to issues of gendered transnational processes, might contribute to current debates. Copyright © 2004 John Wiley & Sons, Ltd.
Keywords: amériques; approches et analyses; asie; canada; cours; discipline; géographie; histoire et politique; inde; mariage; mariages transnationaux; migration; premier cycle; punjab; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques